A Systematic Review of Reproductive Adaptation and Management Strategies of Tropical Cattle under Heat Stress in Kalimantan - Arifin, Dani Nur; Rizkuna, Akhmat; Aprylasari, Dede (CV. Komunitas Dunia Peternakan, 2025)
Unpredictable climate fluctuations are now a challenge to the survival of livestock, one of the largest food commodities in Kalimantan. As one of Indonesia's largest island, straddled by the equator, has a tropical climate that frequently experiences culmination phenomena due to year-round sunlight. This study aims to analyze livestock suitable for breeding in Kalimantan, considering various criteria from a reproductive perspective. This review integrates recent empirical studies and regional data to evaluate reproductive responses, adaptive physiology, and management strategies of tropical cattle under the environmental stressors typical of Kalimantan. Data collection will present various data on livestock in extreme hot environments from various parts of the world, which can reproduce well as a reference for adoption in Kalimantan. The novelty of this study lies in its synthesis of tropical reproductive physiology with practical interventions specific to Kalimantan’s humid equatorial environment. Recommended adaptive strategies include selective breeding for heat-tolerant genotypes, nutritional fulfillment, water supply, and thermal housing management. Collectively, these measures strengthen the resilience of tropical cattle production systems, improving food security and sustainability under climate variability.